IMPLEMENTATION OF SHARIAH COMPLIANCE FOR HYBRID CONTRACT PRODUCTS AT BAITUL MAL WAT TAMWIL IN INDONESIA - Syakira, Yulia Rachma; Rahman, Taufiqur (Reflektika, 2024)
One of the ways carried out by Baitul Mal wat Tamwil institutions in order to attract customer interest and meet the demands of modern society is the development of hibryd contracts (multi-contracts) which in practice the use of these multi-contracts often experiences shifts and deviations from the principles that have been regulated in sharia provisions. This study has several objectives, among others, first to determine the application of multiple contracts in Baitul mal wat Tamwil institutions, in this case there are two institutions that are the object of research, namely BMT Makin Amin and BMT Nuansa Umat. Second, to determine sharia compliance in the application of multiple contracts applied to the two BMT. This research uses a qualitative method with an indepth analysis model, where researchers in conducting this research use several data sources ranging from literature studies, surveys and discussions with BMT and related sources. The approach used by the author is a normative-empirical approach by examining the implementation of contracts applied to Baitul Mal Wat Tamwil (BMT). The results of this study indicate that there are two hybrid models applied in the two BMTs, among others, Murabahah bil wakalah and Ijarah muntahiya Bit Tamlik (IMBT) Where in its implementation the two BMTs have shown their compliance, this is evidenced by the conformity between the DSN-MUI fatwa and the practices carried out by the two BMT.